Bewertung der Tiergerechtheit in der intensiven Hähnchenmast durch Bürger anhand von Bildern: Ein Survey-Experiment; Citizens' Evaluation of Animal Welfare on Pictures of Intensive Broiler Fattening: A Survey Experiment - Gesa Busch; Carolin Schwetje; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2015)
– Based on media discussion about animal production systems and animal welfare in Germany that mainly relies on pictures, this study analyses the citizen perception of intensive broiler fattening. In a survey experiment, five pictures from a 40,000 broiler barn were shown to citizens. The pictures were taken in the same barn but vary in age of the animals and stocking densities. The sample was split to avoid the five pictures from influencing the perception and each participant was shown only one picture. Overall, the evaluation of the pictures was very negative. Only the picture showing day-old-chicks was perceived as favorable (stocking density: 0.8 kg/m²). This is a challenge for the communication of animal welfare standards because the reductions, inter alia currently being discussed in science and politics of stocking densities were not perceived as an animal welfare advantage from a citizen perspective.
Keywords: 330